346 Baroreflex sensitivity and autonomic function in Takotsubo syndrome long after the acute phase. (8th December 2021) - Zinelli, Martina; Lazzeroni, Davide; Moderato, Luca; Centorbi, Claudio Stefano; Bini, Matteo; Magnani, Giulia; Brambilla, Lorenzo; Castiglioni, Paolo; Piepoli, Massimo; Cabassi, Aderville; Ardissino, Diego; Coruzzi, Paolo; et al.
Abstract: Aims: Takotsubo Syndrome (TS) occurs as an acute coronary syndrome (ACS) characterized by severe left ventricular (LV) dysfunction that typically recovers spontaneously within days or weeks and in the absence of obstructive coronary artery disease. Although during the acute phase it is well documented that an exaggerated sympathetic tone plays a central role in the development of TS, whether an impaired sympatho-vagal balance may persist long after the acute phase, despite the recovery of left ventricular function, is still an open issue. Interestingly, recent evidences suggest that an impairment in central autonomic network not only persist long after the acute event but also may be pre-existent before the acute onset of TS. The Aim of the study was to investigate whether an impairment of the autonomic function is still present long after a TS event. Methods and results: We evaluated 67 patients (91% female, mean age 66 ± 8 years) divided into three groups: 24 with a history of TS (1 year after acute event), 21 subjects with a previous history of acute coronary syndrome (ACS) and complete LV ejection fraction recovery (1 year after acute event) and 22 age- and gender-matched healthy subjects. All patients underwent a non-invasive beat-to-beat arterial blood pressure and heart rate recording (short term: 5 min), after at least 3 days of β-blockers wash-out, to obtain heart rate variability (HRV) and spontaneous baroreflex sensitivity (sBRS) data. An overall autonomic dysfunction was found in both TS and ACS groups compared to controls. In particular, a lower heart rate variability, expressed as lower SDNN, has been found in TS and ACS groups compared to controls (31 ± 12 vs. 25 ± 11 vs. 41 ± 22; P  = 0.006—Figure A ) as a consequence of blunted vagal tone, expressed as lower RMSSD (20 ± 12 vs. 19 ± 11 vs. 40 ± 37; P  = 0.007—Figure B ) and higher sympathetic tone, expressed as higher LF/HF ratio ( P  = 0.007 Figure C ) which was found to be higher in TS even when compared to ACS (TS: 3.5 ± 2.5 vs. ACS: 2.1 ± 1.7; P  = 0.011). Moreover, fractal analysis of HRV showed higher complexity of heart rate regulation, expressed as higher fractal dimension (DFA 1.48 ± 0.06 vs. 1.53 ± 0.05 vs. 1.40 ± 0.10; P  < 0.0001—Figure D ), in both TS and ACS compared to controls. Interestingly, spontaneous BRS showed the lowest values in the TS group (sSBP: 5.6 ± 2.6 vs. 7.5 ± 3.0 vs. 12.1 ± 11.9; P  = 0.027—Figure E ), associated with highest levels of sympathetic peripheral control of systolic blood pressure (SBP), expressed as LF-BRS (13.7 ± 9.6 vs. 8.3 ± 5.2 ± 6.8 ± 5.8; P  = 0.008—Figure F ). Conclusions: An autonomic dysfunction, characterized by a hyper-sympathetic tone, reduced baroreflex sensitivity and increased peripheral adrenergic control of blood pressure, persists in TS patients long after the acute phase.